Book Review: Glossary of Prehistoric and Historic Timber Buildings by Lutz Volmer and W. Haio Zimmermann (ed.) - Roeland P Paardekooper (EXARC Journal)
The 1987 conference in Århus, Denmark on ESF Workshop on the reconstruction of wooden buildings from the prehistoric and early historic period has been important to EXARC as we have acquired, and are gradually publishing, the manuscripts of the unpublished proceedings.